Electrochemical Mechanism Investigation of Cu2MoS4 Hollow Nanospheres for Fast and Stable Sodium Ion Storage - Chen, Jingwei; Mohrhusen, Lars; Ali, Ghulam; Li, Shaohui; Chung, Kyung Yoon; Al-Shamery, Katharina; Lee, Pooi See (WILEY-V C H VERLAG GMBH, 2019)
Sodium ion batteries (SIBs) are promising alternatives to lithium ion batteries with advantages of cost effectiveness. Metal sulfides as emerging SIB anodes have relatively high electronic conductivity and high theoretical capacity, however, large volume change during electrochemical testing often leads to unsatisfactory electrochemical performance. Herein bimetallic sulfide Cu2MoS4 (CMS) with layered crystal structures are prepared with glucose addition (CMS1), resulting in the formation of hollow nanospheres that endow large interlayer spacing, benefitting the rate performance and cycling stability. The electrochemical mechanisms of CMS1 are investigated using ex situ X-ray photoelectron spectroscopy and in situ X-ray absorption spectroscopy, revealing the conversion-based mechanism in carbonate electrolyte and intercalation-based mechanism in ether-electrolyte, thus allowing fast and reversible Na+ storage. With further introduction of reduced graphene oxide (rGO), CMS1-rGO composites are obtained, maintaining the hollow structure of CMS1. CMS1-rGO delivers excellent rate performance (258 mAh g(-1) at 50 mA g(-1) and 131.9 mAh g(-1) at 5000 mA g(-1)) and notably enhanced cycling stability (95.6% after 2000 cycles). A full cell SIB is assembled by coupling CMS1-rGO with Na3V2(PO4)(3)-based cathode, delivering excellent cycling stability (75.5% after 500 cycles). The excellent rate performance and cycling stability emphasize the advantage of CMS1-rGO toward advanced SIB full cells assembly.
Keywords: GRAPHENE OXIDE COMPOSITE; SUPERIOR RATE CAPABILITY; CHEVREL-PHASE COMPOUND; X-RAY-ABSORPTION; LONG-CYCLE LIFE; ANODE MATERIAL; HIGH-CAPACITY; STRUCTURAL-CHARACTERIZATION; BATTERIES; PERFORMANCE